2022
DOI: 10.1113/jp282168
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of background Ca2+ influx, sarcoplasmic reticulum threshold and heart failure in determining propensity for Ca2+ waves in sheep heart

Abstract: support-information-section).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Nevertheless, although our suggestions of a possible role of background influx in the pathophysiology of AF remain highly speculative, what remains certain is that the findings of Hutchings et al (2022) pose an important question of whether background Ca 2+ influx could be a 'lead actor' in the 'cinematic' pathophysiology of arrhythmia, or an insignificant 'extra' . Therefore, further research is necessary to establish the role of background Ca 2+ influx in this 'movie' called arrhythmia.…”
Section: Subsequent To the Seminal Experiments Bymentioning
confidence: 96%
See 2 more Smart Citations
“…Nevertheless, although our suggestions of a possible role of background influx in the pathophysiology of AF remain highly speculative, what remains certain is that the findings of Hutchings et al (2022) pose an important question of whether background Ca 2+ influx could be a 'lead actor' in the 'cinematic' pathophysiology of arrhythmia, or an insignificant 'extra' . Therefore, further research is necessary to establish the role of background Ca 2+ influx in this 'movie' called arrhythmia.…”
Section: Subsequent To the Seminal Experiments Bymentioning
confidence: 96%
“…Interestingly, in addition to the study outcome exempting the contribution of NCX to the observed background Ca 2+ influx via its reverse mode Na + /Ca 2+ exchange, Hutchings et al. (2022) demonstrated that connexins and some members of the TRPC family, that is TRPC1/4/5, did not contribute to the background influx responsible for the SR Ca 2+ overload in the sheep ventricular myocytes. Instead, TRPC6 was found to be a key contributor to the background Ca 2+ entry in ventricular myocytes exposed to elevated extracellular Ca 2+ .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, Hutchings et al. (2022) nicely revealed that SR Ca 2+ overload and spontaneous Ca 2+ waves induced by such supra‐physiological levels of [Ca 2+ ] o were due primarily to TRPC6‐mediated Ca 2+ influx instead of LTCC and NCX. The pronounced effect of high [Ca 2+ ] o on spontaneous Ca 2+ waves supports the pro‐arrhythmic effect of hypercalcaemia in HF.…”
Section: Parameters Control Heart Failurementioning
confidence: 99%
“…In a recent study published in The Journal of Physiology , Hutchings et al. (2022) investigated the mechanisms underlying cardiomyocyte Ca 2+ entry in the presence of high concentrations of extracellular Ca 2+ ([Ca 2+ ] o ) and its contribution to the generation of spontaneous Ca 2+ waves in a large‐animal HF model. HF was induced in sheep by right‐ventricular tachypacing and diagnosed based on symptoms (i.e.…”
Section: Parameters Control Heart Failurementioning
confidence: 99%